"She is the Best Female Coach": Female Swimming Coaches' Experiences of Sexism - Jessica L. Siegele; Robin Hardin; Elizabeth A. Taylor; Allison B. Smith (University of Kansas Libraries, 2020)
Sport participation for women and girls is at an all-time high in the United States, but women are still widely underrepresented in leadership positions and coaching (Acosta & Carpenter, 2014). Women hold approximately 50% of head coaching positions of women's teams in the National Collegiate Athletic Association, and only 18% of the head coaching positions of women's swimming and diving teams (LaVoi & Silva-Breen, 2018). Numerous barriers have been identified through previous research on the factors that inhibit upward career mobility for female coaches. Semi-structured interviews were used to examine the career experiences of 21 current or former female swimming coaches at the NCAA Division I level. The theme of sexism in coaching was pervasive and identified in five different categories: (a) misidentification, (b) differential treatment, (c) isolation, (d) tokenism, and (e) motherhood. The sexism that female coaches experience hinders upward career mobility which can lead to career dissatisfaction and early exits from the field, contributing to the underrepresentation of women in the profession.